Studi Efisiensi Pembakaran Pada Pembakaran Fluidized Bed Limbah Medis - Pratama Ginting, Febyoga; Suprapta Winaya, I Nyoman; Lokantara, I Putu (Teknik Desain Mekanika, 2021)
Abstract Medical waste is infectious waste, so it is necessary to manage medical waste to reduce the negative impact caused by medical waste. This study aims to reduce medical waste by using fluidized bed combustion technology to calculate its combustion efficiency. Fluidized bed combustion is a technology that is able to reduce medical waste to ash and has a high combustion efficiency. This study was conducted by applying experimental studies to determine the influence of bed material particles (silica sand, alumina sand, and zeolite sand) on combustion efficiency in fluidized bed combustion. The result of this study showed the combustion of the three variations of bed material with a diameter of bed material 0,5 nn, silica sand is a bed material that has the highest combustion efficiency of 96,73 %. Keywords : Efficiency, Medical Waste, Fluidized Bed, Combustion